2007
DOI: 10.1021/ac0708588
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Effects of Gender, Diurnal Variation, and Age in Human Urinary Metabolomic Profiles

Abstract: Metabolomics may have the capacity to revolutionize disease diagnosis through the identification of scores of metabolites that vary during environmental, pathogenic, or toxicological insult. NMR spectroscopy has become one of the main tools for measuring these changes since an NMR spectrum can accurately identify metabolites and their concentrations. The predominant approach in analyzing NMR data has been through the technique of spectral binning. However, identification of spectral areas in an NMR spectrum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
361
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 371 publications
(398 citation statements)
references
References 68 publications
35
361
0
2
Order By: Relevance
“…Sex-based differential expression of human corneal epithelial cells has also demonstrated that one of the enriched pathways is the DNA replication pathway (25). Similarly, sex differences in the expression of TCA cycle enzymes in skeletal muscle (26), and the excretion of citrate in urine (27), have been demonstrated. Together, the sex-specific pathways enriched in our analysis have previously been shown to differ between sexes, albeit in different tissues.…”
Section: Discussionmentioning
confidence: 87%
“…Sex-based differential expression of human corneal epithelial cells has also demonstrated that one of the enriched pathways is the DNA replication pathway (25). Similarly, sex differences in the expression of TCA cycle enzymes in skeletal muscle (26), and the excretion of citrate in urine (27), have been demonstrated. Together, the sex-specific pathways enriched in our analysis have previously been shown to differ between sexes, albeit in different tissues.…”
Section: Discussionmentioning
confidence: 87%
“…Sample (600 mL) was subsequently transferred into 5 mm 535 pp NMR tubes (Wilmad LabGlass), and samples were stored at 4 C until NMR acquisition (within 24 hours of sample preparation). NMR spectra were acquired as previously described (7).…”
Section: Data Collectionmentioning
confidence: 99%
“…We have shown that NMR spectroscopy coupled with targeted profiling techniques offers a powerful approach to generate high-density metabolic data on biofluids (3)(4)(5)(6)(7)(8). Multivariate statistical analysis, including principal component analysis (PCA), partial least-squares-discriminant analysis (PLS-DA), or orthogonal partial least-squares-discriminant analysis (OPLS-DA) can be applied to these data or complex spectral data to aid in the characterization of changes related to a biological perturbation or disease.…”
mentioning
confidence: 99%
“…Inherent variability can be minimized by collecting samples in the morning (08:30-09:30) preferably before food intake (33,34). For biofluids, the optimal sample volume is 0.1 to 0.5 ml.…”
Section: Sample Handling and Preparationmentioning
confidence: 99%